Supplementation of Biotin to the Semen Dilution Medium Improves Sperm Quality Parameters in Turkeys - Bazpour, Marziyeh; Tabatabaei Vakili, Saleh; Mirzadeh, Khalil; Aghaei, Ali (Archives of Veterinary Science, 2025)
Turkey's reproduction relies heavily on artificial insemination, making short-term semen preservation crucial. This study investigated the impact of biotin supplementation on turkey sperm quality during short-term cold storage. Semen was diluted with extenders containing various biotin concentrations (0, 25, 50, 100, and 200 nmol) and stored at 5°C for 24 hours. While initial sperm quality was unaffected by biotin levels, prolonged storage revealed significant differences. A biotin concentration of 25 nmol consistently outperformed other levels in maintaining sperm motility, viability, and membrane integrity, with the lowest rates of morphological abnormalities. Conversely, a 200 nmol biotin concentration negatively impacted sperm viability (P < 0.05). For each treatment, 25 nmol of biotin consistently preserved the best sperm quality and viability (P < 0.05). These findings suggest that adding 25 nmol of biotin to turkey semen extenders is an effective strategy for preserving sperm quality and extending its lifespan under cold storage conditions.